Medicinal Plants Conservation and Sustainable Use Through Forest Gene Banks - Srinivasamurthy, T. S.; Karnat, Mohan; Prabhakaran, V.; Elkunchwar, S. N.; Ravikumar, K.; Ghate, Utkarsh; Jadhav, Satish (Indian Forester, 2003)
State Forest Departments (SFDs) of Andhra Pradesh , Karnataka , Kerala ,Tamil Nadu and Maharashtra , in consultation with FRLHT and the support of DANIIDA and UNDP have established 54 forest gene banks sites termed 'Medicinal Plant Conservation Areas (MPCA)'. The network of 54 MPCAs measuring 200 ha to 500 ha each established gradually since 1993 represents all forest types and large bio-climatic and soil regime variation. These gene banks harbour recorded populations of 45% of flowering and medicinal plants of Peninsular India , including 70% of the red listed. The intra-specific diversity i.e. germplasm conserved in the MPCA network can be used to provide authenticated quality planting material for commercial cultivation to meet rising demands of the herbal industry. MPCAs also constitute 'study sites' for threatened species recovery research. MPCAs have proved crucial in capacity building of forestry staff , local communities and researchers in the conservation of Medicinal Plants for sustainable use and equitable benefit sharing. This experience can help in implementing plans and programmes under the Biological Diversity Act 2002 , National Biodiversity Strategy and Action Plan (NBSAP) and Medicinal Plants Board.